Norm Localization of Carbon Market Transfer from the European Union to China: Development of the Emissions Trading System - Gravenia Rahma Safira (LifeSciFi, 2026)
This article examines how China localized the global carbon market norm, particularly the European Union Emissions Trading System (EU ETS), within its domestic climate governance framework. Using a qualitative approach grounded in constructivist International Relations theory and Amitav Acharya’s norm localization framework, the study analyzes how international norms were adapted to fit China’s political and institutional context. The findings show that China did not directly replicate the European cap-and-trade model. Instead, policymakers selectively reconstructed the norm through policy learning, domestic framing, grafting onto existing governance practices, and pruning elements considered incompatible with national priorities. China’s ETS evolved into a hybrid model characterized by intensity-based benchmarking, free allocation, output-based adjustment, sectoral sequencing, and strong state supervision. The regional pilot schemes (2013–2014) and the national ETS launched in 2021 demonstrate this localization process. The study concludes that norm localization increased the domestic legitimacy and institutional compatibility of China’s ETS, although it also created challenges such as weak carbon price signals, limited market liquidity, and uneven implementation. This article contributes to International Relations scholarship by showing that climate norm diffusion involves active translation rather than simple policy transfer.